Expression of ORAI1, a Plasma Membrane Resident Subunit of the CRAC Channel, in Rodent and Non-rodent Species. (December 2014) - Guzman, Roberto; Valente, Eliane G.; Pretorius, Jim; Pacheco, Efrain; Qi, Meiying; Bennett, Brian D.; Fong, David H.; Lin, Fen-Fen; Bi, Vivian; McBride, Helen J.
We determined the expression of ORAI1 protein in rodent and non-rodent tissues using a monoclonal antibody directed against an extracellular loop of the protein. Previous reports using antibodies directed at the C-terminus of ORAI1 have not detected central nervous system (CNS) expression. Our results demonstrate broad tissue expression that includes the CNS using a unique monoclonal antibody specific to an extracellular loop of ORAI1. In addition, we present in situ hybridization (ISH) results using a probe within the middle of the mouse coding region showing CNS expression of Orai1 RNA. We contrast the patterns of rodent and human tissue expression and conclude that rodents have similar expression of ORAI1 in most tissue types when compared to primates, with an important exception being the male reproductive system, where human-specific expression is observed.